Persistent Lymphadenopathy due to IgG4-Related Disease - Benjamin Smith; Matthew B. Carroll (Case Reports in Immunology)
A 28-year-old healthy female presented to her primary care physician with lymphadenopathy, fatigue, malaise, and night sweats. Symptoms persisted despite conservative treatment and eventually the patient underwent multiple lymph node resections and a bone marrow biopsy before a diagnosis of IgG4-related disease (IgG4-RD) was made. IgG4-RD is a relatively new disorder first histopathologically recognized within the last decade. As the disease can affect a single organ or multiple organs, symptoms can vary greatly among patients. With symptoms ranging from mild, such as lower extremity edema, to severe, such as spinal cord compression, IgG4-RD must be considered in appropriate patients. Diagnostic criteria have been proposed based on organ involvement, serum IgG4 levels, and histopathological criteria. Diagnosis can be difficult to make with many studies suggesting different values for diagnostic criteria, such as the level of tissue IgG4+/IgG+ cell ratio to delineate IgG4-RD. Treatment consists of high dose glucocorticoids as a first line therapy with some patients choosing instead to simply undergo observation. This case illustrates the difficulty in diagnosis and the need for increased awareness among medical professionals.